Oblique impact of frictionless spheres: On the limitations of hard sphere models for granular dynamics - Müller, Patric; Pöschel, Thorsten (Granular Matter, 2012)
When granular systems are modeled by hard spheres, particle-particle collisions are considered as instantaneous events. This implies that while the velocities change according to the collision rule, the positions of the particles are the same before and after such an event. We show that depending on the material and system parameters, this assumption may fail. For the case of viscoelastic particles we present a universal condition which allows to assess whether hard-spheremodeling and, thus, event-driven Molecular Dynamics simulations are justified. © Springer-Verlag 2012.
Keywords: Coefficient of normal restitution; Event-driven molecular dynamics; Granular gases; Hard sphere model; Viscoelastic spheres